The Contribution of Public Health Investments to the Economic Growth of Cameroon - Amadu, Ismaila; Eseokwea, Ngoe Fritz; Ngambi, Marcel (International Journal of Social Sciences and Management, 2017)
The goal of this paper is to determine the contribution of public health investments to the economic growth of Cameroon. The study used the human capital model of Lucas (1988) within the framework of endogenous growth theories. The Vector Error Correction Model (VECM) was employed in the estimations procedure using the World Development Indicators (WDI, 2013) data from the World Bank over the period spanning from 1988 to 2013.The findings show that government health expenditures contribute to economic growth only in the long run. From our results, we recommend that: first, the government should increase health spending to 10 or 15 percent of its GDP as initially suggested by the African Union and the World Health Organization respectively; second, government should enhance the provision of health care services by the private sector by putting in place incitation measures; third, competitive awards should be granted to those health units that render quality health care services. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 12-21